Evaluating Behavior Modification for Tantrums in Early Childhood: Approaches for Enhanced Management and Intervention - Ratri Ningdyah Utari, Sinta; Khusniatul Amanah, Siti; Amellya Jariyah, MaÔÇÖrifatul; Dey Dias Wardini, Aprilia; Abdul Latif, Muhammad; Mei Sabandal, Glory (Indonesian Journal of Early Childhood Educational Research (IJECER), 2023)
Negative behaviors in children, such as tantrums, are common during early childhood due to inherent egocentric tendencies. Tantrums, if not addressed by parents, can potentially harm the child. Therefore, parents need to employ early-stage behavioral modification techniques to manage tantrums in children, with continuous evaluation. This study focuses on evaluating the modification of tantrum behavior in early childhood, involving a series of procedures to transform negative behaviors into positive ones. The evaluation, as the final stage of the behavior modification process, assesses whether the treated behavior has undergone significant changes by observing and recording its persistence. The research adopts a qualitative approach, utilizing structured interviews for data collection from parents as informants. Data analysis follows the Milles and Huberman model. Purposively selected subjects, children aged 2-6 years, are obtained through interviews and in-depth observations. Results indicate that effective reinforcing actions involve allowing children to express emotions under parental supervision, preventing harm while calming the child through comforting gestures. The final evaluation reveals that children exhibit increased freedom in expressing emotions, yet still under parental supervision. ┬á